Students' Reflections on the Benefits of a Financial Simulation Through "Thank You Notes". Issue 6 (2nd November 2019) - Mupinga, Davison M.; Caniglia, Joanne
Abstract: As an instructional strategy, simulations have become common in the field of education. While they have been effective at imparting knowledge and skills, not all simulation experiences meet their objectives. This study determined the effectiveness of a financial simulation, the Reality Store®, aimed at teaching financial literacy and life skills to youth. Data were collected from Thank You notes written by middle school students who had participated in the simulation. These notes were combined with data from post-simulation surveys to ensure trustworthy results. Overall, students were satisfied with the simulation experience and learned that: adult life is hard; children are expensive; and the need for budgeting and saving money is essential. Recommendations for teaching financial literacy and life skills using simulations are provided.